2022
DOI: 10.3389/fcimb.2022.1009894
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and analysis of risk factors for disease progression of patients with SARS-CoV-2 Omicron variant infection: A retrospective study of 25207 cases in a Fangcang hospital

Abstract: ObjectivesTo summarize the clinical characteristics of patients infected by SARS-CoV-2 omicron variant and explore the risk factors affecting the progression in a Fangcang hospital, Shanghai, China.MethodsA total of 25,207 patients were retrospectively enrolled. We described the clinical characteristics and performed univariate and multivariate logistic regression analysis to identify the risk factors for non-severe to severe COVID-19 or death.ResultsAccording to the outcomes, there were 39 severe patients (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…In addition, it was demonstrated that old age is an independent risk factor associated with prolonged viral shedding duration, which was in line with previous studies 36,37 . However, a retrospective study on a large sample of Fangcang hospital cases infected by the SARS‐CoV‐2 omicron variant showed that age, fever, cough, fatigue, and comorbidity are predictors for the deterioration of SARS‐CoV‐2 omicron variant infection 38 . In that study, different from ours, the researchers compared the clinical characteristics between non‐severe patients and severe patients, and identified the risk factors for severe COVID‐19 infection.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, it was demonstrated that old age is an independent risk factor associated with prolonged viral shedding duration, which was in line with previous studies 36,37 . However, a retrospective study on a large sample of Fangcang hospital cases infected by the SARS‐CoV‐2 omicron variant showed that age, fever, cough, fatigue, and comorbidity are predictors for the deterioration of SARS‐CoV‐2 omicron variant infection 38 . In that study, different from ours, the researchers compared the clinical characteristics between non‐severe patients and severe patients, and identified the risk factors for severe COVID‐19 infection.…”
Section: Discussionsupporting
confidence: 87%
“…Our results are consistent with an observational study that the majority of patients infected with the SARS-CoV-2 Omicron variant are asymptomatic or mild COVID-19 [11], suggesting a reduced pathogenicity of Omicron variants [12,13]. Nevertheless, the unique biological characteristics of Omicron variants increase the transmissibility, particularly in asymptomatic COVID-19 patients [14].…”
Section: Discussionsupporting
confidence: 91%
“…Hospitalization rate, hospitalization length, and death rate of patients infected with omicron variant have declined relative to those infected with other variants, and the symptoms are less severe [6][7][8]. However, omicron has more than 50 mutations and different amino acids in the spike protein, which poses a large threat to elderly patients with no vaccination and chronic comorbidities owing to the disordered immune system, making treatment difficult for these patients [4,9,10]. It has been reported that the omicron variant is resistant to the treatment of convalescent plasma and most neutralizing nonoclonal antibodies [11].…”
Section: Introductionmentioning
confidence: 99%